Pembuatan Rocket Stove Ramah Lingkungan untuk Masyarakat Desa Cibugel, Cisoka: Studi Pengabdian kepada Masyarakat - Novela Wulandari; Shalsa Aullya Puteri; Achmad Riqqil Fajri; Yusril Ibrahim; Maria Desy Nataliani (Universitas Pahlawan Tuanku Tambusai, 2026)
The majority of residents of Cibugel Village, Cisoka District, still rely on traditional wood-fueled stoves that produce excessive smoke, are energy-inefficient, and have negative impacts on health and the environment. This community service activity aims to introduce and train residents in making oil stoves as an alternative energy-saving stove that produces minimal smoke and utilizes used oil fuel, which is widely available in the surrounding environment. The activity methods include needs surveys, training in making oil stoves using lightweight iron, testing combustion efficiency, and usage assistance. The results show that the oil stoves are capable of producing stable heat, are economical, and reduce dependence on firewood by up to 100%. Residents consider oil stoves more practical and environmentally friendly because they do not produce thick smoke like traditional stoves. This program proves that the oil stove innovation is an effective and sustainable solution to meet the cooking needs of rural communities.